2007
DOI: 10.1161/hypertensionaha.106.076083
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Chemoreceptors and Sympathetic Nerve Activity

Abstract: C hronic elevation in sympathetic nerve activity (SNA) is associated with the development and maintenance of certain types of hypertension 1 and contributes to the progression of chronic heart failure (CHF). 2 The mechanisms involved in sympathetic dysfunction in these disorders appear to be complex and multifactorial. A unified hypothesis is likely to encompass alterations in multiple autonomic reflex pathways, central integratory sites, and chemical mediators that control sympathetic outflow. For example, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 70 publications
(119 reference statements)
2
46
0
Order By: Relevance
“…The contribution of this haem-containing enzyme to H 2 S generation likely decreases under conditions of hyperhomocysteinaemia; gasotransmitter synthesis is relatively insensitive to Hcy, indicating that cystathionine c-lyase is largely responsible for enhancing H 2 S generation under conditions of hyperhomocysteinaemia. These findings, it has been suggested, point to an important new role for cystathionine c-lyase in the thiol metabolome and Hcy management (Singh et al 2009) and, as the present data indicate, in contributing to a significant clinical phenotype associated with substantial rates of morbidity and mortality (Kearney et al 2005;Reynolds et al 2007;Inoue et al 2007;Elliott 2005;Schultz et al 2007;Paoletti et al 2006;Parnetti et al 2004;Zylberstein et al 2004;Boushey et al 1995;Zhou et al 2001;Sutton-Tyrell et al 1997;Nygard et al 1997). Since H 2 S is highly reactive and has long been considered as toxic, its impact on various tissues is well characterised, but with recent advances in our knowledge, implicating H 2 S in Alzheimer's disease, epilepsy and stroke (Gadalla and Snyder 2010;Gupta et al 2010) as well as hypertension, future development of drugs specifically modulating H 2 S levels is likely to prove beneficial (Gupta et al 2010).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The contribution of this haem-containing enzyme to H 2 S generation likely decreases under conditions of hyperhomocysteinaemia; gasotransmitter synthesis is relatively insensitive to Hcy, indicating that cystathionine c-lyase is largely responsible for enhancing H 2 S generation under conditions of hyperhomocysteinaemia. These findings, it has been suggested, point to an important new role for cystathionine c-lyase in the thiol metabolome and Hcy management (Singh et al 2009) and, as the present data indicate, in contributing to a significant clinical phenotype associated with substantial rates of morbidity and mortality (Kearney et al 2005;Reynolds et al 2007;Inoue et al 2007;Elliott 2005;Schultz et al 2007;Paoletti et al 2006;Parnetti et al 2004;Zylberstein et al 2004;Boushey et al 1995;Zhou et al 2001;Sutton-Tyrell et al 1997;Nygard et al 1997). Since H 2 S is highly reactive and has long been considered as toxic, its impact on various tissues is well characterised, but with recent advances in our knowledge, implicating H 2 S in Alzheimer's disease, epilepsy and stroke (Gadalla and Snyder 2010;Gupta et al 2010) as well as hypertension, future development of drugs specifically modulating H 2 S levels is likely to prove beneficial (Gupta et al 2010).…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, there is a clear association between occurrence of stroke (Inoue et al 2007), myocardial infarction (Elliott 2005), heart failure (Schultz et al 2007) and kidney disease (Paoletti et al 2006), and the degree of hypertension. Despite this, the pathoaetiology of hypertension has still not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…During the airflow occlusion, the resulting hypoxia and hypercapnia stimulates the carotid body chemoreceptors producing reflex ventilatory, sympathetic and hypertensive responses. Among these disturbances, the chronic intermittent hypoxia is considered the main factor for the development of the hypertension [1,19,33,41,43,51,55,56,82,83,88,93,100]. However, conclusions from studies performed in OSA patients are partial and somehow controversial, because invasive procedures are precluded because of ethical reasons in humans, and OSA patients often present concomitant morbidities (i.e.…”
Section: Pathogenic Mechanisms Of the Hypertension Induced By Osamentioning
confidence: 99%
“…
In the late 20 th century, it was found that the basic function of the CB is chemical control of the regulation of respiratory action by means of a reflex from chemoreceptors, but it was not until the last 15 years that research has revealed another important function: the chemoreceptors present in the CB play an essential role in regulating the functions of the circulatory system [3][4][5]. Research connected with the carotid body is currently focused on establishing the significance of chronically increased CB activity in the progression of heart failure and in the genesis of hypertension [6][7][8][9].
…”
mentioning
confidence: 99%